Purum taçque coya, Virgen Maria: The Feminine Sacred and the Virgin Mary in Sixteenth- and Seventeenth-Century Quechua Doctrinal Texts - Gruda, Szymon (Entangled Religions, 2023)
The paper offers an analysis of Quechua words and phrases used in reference to the Virgin Mary in four doctrinal works published between 1585 and 1631. The objective of the analysis is to determine the strategies of intercultural translation employed by the authors of the texts and to reconstruct the possible reception on the part of their intended audience. The analysis reveals that, apart from the formulae adapted from the European tradition, the authors drew the means of expression from precontact Andean religion and culture, especially from its ways of referencing religiously important female figures: the Quya and the female deities. This practice was most probably based on an assumption on the part of the authors that the connotations of Quechua words and phrases used by them corresponded to those which formed part of the established practice of Marian devotion in the Western Christendom. It enabled, however, a reading of the texts that construes a figure of Mary as analogous, perhaps even identical in some aspects, to female deities of the Andean religion.